Rediscovering Australian brands : the roles of categorization theory and confirmation bias on country of ownership cues - Cheah, Isaac (Curtin University, 2010)
The study examines the effect of country of ownership cues, economic nationalistic and consumer ethnocentric tendencies with regards to product judgments and purchase intentions of Australian wines with multi country affiliations. To test the research model, a specific scale to measure and conceptualise economic nationalistic tendencies (CENTSCALE) was developed and a new construct “consumer willingness to buy hybrid products” was created.